IMPLEMENTASI KEPEMIMPINAN DAN MANAJEMEN DALAM LEMBAGA PENDIDIKAN - Mumuh Muhtarom (Balai Diklat Keagamaan Bandung, 2018)
In educational institutions, the existence of a head as a leader is very important and strategic. He acts and functions as the regulator and manager of educational institutions so that they work well and effectively. So leadership can be understood as a process of influencing in determining organizational goals, motivating followers' behavior to achieve goals, influencing to improve their groups and culture. Besides that it also influences the interpretation of events on followers, organization, and activities to achieve goals, maintain working relationships and group work, the acquisition of support for cooperation from people outside the group or organization. While education management is the process of planning, organizing, implementing, and controlling in managing resources in the form of Man, Money, Materials, Method, Machines, Market, Minute and Information to achieve effective and efficient goals in the field of education. So the purpose of this study wants to know the implementation of leadership and management in educational institutions according to experts in their fields. Key words: Effective, Leadership, Management, Implementation, Education